RANCANG BANGUN ALAT UKUR KETINGGIAN PERMUKAAN AIR SUNGAI MENGGUNAKAN SENSOR ULTRASONIK AJ-SR04M - Yasir Abdan Syakur; Elohansen Padang; Baina Afkril (FMIPA Universitas Papua, 2023)
Monitoring of water levels provides many benefits in various fields of application such as flood disaster mitigation, irrigation management, and dam management. Research has been carried out on the design and testing of a river water level measuring instrument based on the AJ-SR04M ultrasonic sensor. This ultrasonic sensor has several advantages, including accurate measurement results, low costs, can be found easily on the market, simple, and waterproof making it suitable for river water level measurement applications. The developed measuring instrument is also equipped with temperature and humidity sensors as a correction factor for the speed of sound, because these two parameters affect the speed of sound. The Arduino Uno board is used as a signal processing unit in charge of processing all output signals from sensors. The micro SDcard module is used as a container for storing measurement data. Meanwhile, the LCD board is used to display the measurement results. The Arduino Uno board is programmed using the Arduino IDE software. The test results show that the instrument has a very good level of accuracy. This is evidenced by the results of testing the devices which showed a relative error of 0.066%. In addition, the tool also functions with very good precision where the correlation coefficient (R2) obtained from testing the instrument is 0.98.